Oribatid Mites (Oribatida) Associated with Nests of Hollow-Nesting Birds, on the Example of a Model Species, the European Pied Flycatcher (Ficedula hypoleuca), in the Taiga Forests of the European North-East of Russia - Elena N. Melekhina; Andrey N. Korolev; Natalia P. Selivanova (Diversity, 2023)
The authors have obtained original material on the fauna and population structure of oribatid mites inhabiting nests of the European Pied Flycatcher (Ficedula hypoleuca, Passeriformes, hollow-nesting bird) on the territory of the taiga zone of the European North-East of Russia. Long-term research and the collection of nests were carried out in the green zone of Syktyvkar in 2017–2022. Observations were made for artificial nests (hollows) of a box type with a bottom area of 100 cm2. The material of the tray was collected completely. In 135 studied nests of Pied Flycatchers, 1762 specimens were found and identified for 22 species of oribatid mites from 19 genera and 16 families. In the nests of the Pied Flycatcher, a complex of species was found that is known as an arboricolous species for this region; these are Oribatula (Zygoribatula) propinqua, Oribatula (Z.) exilis, Trichoribates (T.) berlesei, and Ameronothrus oblongus. We suggested that arboricolous species, as well as eurytopic species, can actively inhabit bird nests. Highly numerous in our collections were representatives of the Oribatulidae and Scheloribatidae families; they are Oribatula (Z.) propinqua, Oribatula (Z.) exilis, Oribatula (O.) tibialis, and Scheloribates laevigatus. Epigeic species are dominated by the species number. The fauna of oribatid mites mainly included widespread Holarctic species (54.54%).